Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300705
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Good Conversation?

Abstract: Conversational agents promise conversational interaction but fail to deliver. Efforts often emulate functional rules from human speech, without considering key characteristics that conversation must encapsulate. Given its potential in supporting long-term human-agent relationships, it is paramount that HCI focuses efforts on delivering this promise. We aim to understand what people value in conversation and how this should manifest in agents. Findings from a series of semi-structured interviews show people mak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 275 publications
(115 citation statements)
references
References 44 publications
7
84
0
Order By: Relevance
“…This supports the notion that, although they may be perceived through the lens of human dialogue, speech interface dialogues are fundamentally distinct [13,44]. Currently, dialogue interactions with speech-based IPAs tend to be isolated question-answer pairs [44], seemingly functional rather than interpersonal or social in nature [13].…”
Section: Issues With Emulating Aspects Of Humannesssupporting
confidence: 64%
See 2 more Smart Citations
“…This supports the notion that, although they may be perceived through the lens of human dialogue, speech interface dialogues are fundamentally distinct [13,44]. Currently, dialogue interactions with speech-based IPAs tend to be isolated question-answer pairs [44], seemingly functional rather than interpersonal or social in nature [13].…”
Section: Issues With Emulating Aspects Of Humannesssupporting
confidence: 64%
“…For instance, vocal quality clearly maps to work on speech synthesis, where developing more human-like, expressive [1], emotive [39] and personality-filled [51] voices is currently underway. User research has also focused on exploring the role of humanness in partner knowledge assumptions [15], vocal quality [16,37], partner identity [4], linguistic content [13] and conversational interactivity [13,45]. Our work not only identifies the important dimensions of humanness when considering user perceptions, but formalises intuitions by researchers on the types of design decisions that may affect these perceptions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CUI user studies have revealed different meanings of trust however. One study of intelligent personal assistant (IPA) users found many users referring to issues around trust in the CUI's intents, for example regarding identity and privacy protections [3]. Here, users were not concerned with disclosure of sensitive information because of a social uneasiness, but instead because they were unsure how their data would be treated and what data was being collected in the first place.…”
Section: Defining Trustmentioning
confidence: 99%
“…One example of these interfaces is conversational user interfaces (CUIs) which can include text-based dialogue systems, voicebased conversational assistants, embodied virtual agents, and social robots. While CUIs have become increasingly prevalent in the last several years, numerous user studies have revealed that people have concerns about trusting these interfaces [3,4,19]. Nevertheless, there has been little discussion in the community on how to Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%